Uma análise modo-temporal de v1 e dos tipos verbais de v2 nas construções aspectuais [v1andar + v2gerúndio] e [v1viver + v2gerúndio] - Ana Clara Teixeira Ferreira (2022)
The present research aims to investigate the mood-tense contexts in which the auxiliary verb form of the periphrases (here treated as constructions) [V1WALK + V2GERUND] and [V1LIVE + V2GERUND] occur and to understand what types of verbs occupy the V2GERUND position. We address the notions of verbal periphrasis (BARROSO, 1994) and of verbal aspect, to delimit the aspectual meaning expressed by the periphrases, in Castilho (1968), Travaglia (1981), and Barroso (1994). According to these authors, the main aspectual nuances evoked are the iterative and the habitual. The constructions focused on in this study have undergone a process of linguistic change, called grammaticalization, in which the verbs “walk” and “live” no longer have their full lexical content, but show essentially grammatical characteristics as they integrate the constructions in the form of auxiliaries. This research starts from what was determined by Tenuta and Coelho (2018) and Coelho and Tenuta (2020) about the specific grammaticalization process to which these constructions are submitted, in which the auxiliary verbs “walk” and “live”, in their relational sense, had already undergone abstraction and they join the nominal form of gerund to compose the constructions. We consider the periphrases [V1WALK + V2GERUND] and [V1LIVE + V2GERUND] as constructions, according to Goldberg (1995), since the aspectual meaning evoked by them does not come from the compositional sum of their parts, but from the structural whole, globally composed of the auxiliaries “walk” and “live”, in all their possible manifestations of time and manner, together with the gerund nominal form. Occurrences of the constructions discussed here were taken from three corpora, dating from the 20th century, contemporary Portuguese, both in written and oral modalities. These occurrences were identified as reanalyzed (constructions that have already gone through the grammaticalization process), not reanalyzed, or ambiguous; the mood-tense forms of V1WALK/LIVE were listed, so that we could understand which temporal contexts favor the occurrence of the periphrases; the verbs in V2GERUND were classified into states, activities, accomplishments and achievements, according to Vendler (1967). The results were: the most recurrent forms of “walk” are the third person singular and plural present tense and the third person singular past tense (pretérito perfeito), and the most recurrent forms of “live” are the third person singular and plural present tense, as well as the third person singular past imperfective tense (pretérito imperfeito), all indicative. Vendler's (1967) classes that most often go together with V2GERUND are activities and accomplishments. We could conclude that these classes are not always watertight, and several verbs may have features that overlap among them. In addition, we realized that, when integrating the periphrases, V2 verbs gain an activity garb due to the durative essence of the periphrases. These results contribute to the understanding of V2 verbs as well as of the tense and mood of the auxiliary verbs that favor these aspectual constructions.